PROVIDING THE STABLE DEVELOPMENT AND ECONOMIC SUSTAINABILITY OF ENTERPRISES IN THE FACE OF MODERN CHALLENGES - BOKOVETS, Victoria; PILIAVOZ, Tetiana; HRYHORUK, Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article analyzes modern approaches to sustainable development and economic stability of enterprises. It is established that stable development of an enterprise is defined as the ability to continuously grow and function in an unstable economic environment.Economic sustainability of an enterprise is the basis for its stable development. Economic sustainability of an enterprise is interpreted as the ability of an enterprise to maintain its efficiency, competitiveness and financial stability in a dynamic external and internal environment. An integrated approach to economic sustainability covers financial, production, management, market and innovation aspects of the company's activities.The prospects for ensuring stable development and economic sustainability of enterprises lie in the introduction of modern management methods, diversification of activities, staff development and the use of the latest technologies. In addition, it is important to develop partnerships with other enterprises and organizations, which allows them to share experience and resources to achieve common goals.Ensuring stable development and economic sustainability of enterprises is a complex and multifaceted process that requires a systematic approach and consideration of both internal and external factors. The integration of financial, production, innovation and social aspects into the enterprise strategy contributes to its sustainability and competitiveness in the modern economy.The results of the research can be used to improve enterprise management strategies, increase their sustainability and adaptability in the face of modern economic challenges.
Keywords: development; sustainable development; stable development; economic sustainability; social responsibility; environmental safety